'Communists are no Beasts': European Solidarity Campaigns on Behalf of Democracy and Human Rights in Greece and East–West Détente in the 1960s and Early 1970s. (17th October 2017) - CHRISTIAENS, KIM
Abstract : Ever since the collapse of the Greek military regime in 1974 European campaigns over human rights and democracy in Greece have been commonly understood within an anti-totalitarian narrative that has celebrated resistance against both communist dictatorship and right-wing authoritarianism as part of a common journey towards a democratic continent. This article analyses the little-studied history of European solidarity movements with Greece during the 1960s and early 1970s that stretched across both the West and East of the continent. In so doing, it suggests that these campaigns were a facet of the politics of détente and rapprochement that brought together Western and Eastern Europe. Communist peace movements played a central role in these human rights campaigns. This was far from a common anti-totalitarian movement; rather, campaigns for Greece were enmeshed within movements that worked on a wide range of issues – from support for Eastern European dissidents and anti-fascism to world peace and protest against the Vietnam War. Nor were they about 'a return to Europe': above all they thrived on common connections in East and West with the Third World.